Saponins of Panax japonicus Confer Neuroprotection against Brain Aging through Mitochondrial Related Oxidative Stress and Autophagy in Rats - Wan, Jing-zhi; Wang, Rui; Zhou, Zhi-yong; Deng, Li-li; Zhang, Chang-cheng; Liu, Chao-qi; Zhao, Hai-xia; Yuan, Cheng-fu; He, Yu-min; Dun, Yao-yan; Yuan, Ding; Wang, Ting (Current Pharmaceutical Biotechnology, 2020)
Background: Oxidative stress and mitochondrial dysfunction play a vital role in the pathogenesis of brain aging. Saponins from Panax japonicus (SPJ) have attracted much attention for their potential to attenuate age-related oxidative stress as the main ingredient in rhizomes of Panax japonicus. Objective: This study aimed to investigate the neuroprotective effects of SPJ on natural aging rats as well as the underlying mechanisms regarding oxidative stress and mitochondrial pathway. Methods: Sprague-Dawley rats were divided into control groups (3-, 9-, 15- and 24-month old groups) and SPJ-treated groups. For SPJ-treated groups, SPJ were orally administrated to 18-month old rats at doses of 10 mg/kg, 30 mg/kg and 60 mg/kg once daily. Control groups were given the same volume of saline. After the treatment with SPJ or saline for six months, the cortex and hippocampus were rapidly harvested and deposited at -80°C after the rats were decapitated under anesthesia. The neuroprotective effects of SPJ were estimated by histopathological observation, TUNEL detection, biochemical determination and western blotting. Results: SPJ improved pathomorphological changes in neuronal cells and decreased apoptosis in the cortex and hippocampus of aging rats, increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), Na+/K+-ATPase, Ca2+-ATPase and Ca2+/Mg2+-ATPase whereas, decreased malondialdehyde (MDA) contents in the cortex of aging rats. Furthermore, the SPJ increased silent mating type information regulation 2 homolog-1 (SIRT1) protein expression, decreased acetylated level of peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) in the cortex and hippocampus of aging rats, and reversed the aging-induced decline of Forkhead box O3 (Foxo3a), Superoxide Dismutase 2 (SOD2), microtubule-associated protein light chain 3 (LC3II) and Beclin1 levels in the cortex and hippocampus. Conclusion: Our data showed that SPJ conferred neuroprotection partly through the regulation of oxidative stress and mitochondria-related pathways in aging rats.
Keywords: aging